An Evaluation of the Effect of Marmara Family Skills Education_x000D_ Program on Parent’s Self-Efficacy Levels and Support Skills - ÇELİK, BÜŞRA; KÜÇÜKOĞLU, ELİF; ÜNSAL, FATMA ÖZGE; BİLGİN KÖSE, NAZİFE HÜLYA; URAL, OZANA; POLAT, ÖZGÜL; YILDIZ, TUBA (My University, 2021)
The Marmara Family Skills Education Program (MFSEP) is an early intervention program that provides services to families with0- to 3-year-old children, using face-to-face and distance education technologies. This study aims to analyze the effect of MFSEPon parent self efficacy and their skills in promoting the growth of their children. In the research conducted in cooperation with theMarmara University and Mersin Yenişehir Municipality, 17 and 15 volunteer families made up the experimental and control groups,respectively. In other words, the study group comprised a total of 32 families. During the research process, MFSEP material wasgiven to the families in the experimental group, and the MFSEP was implemented with 12 sessions over 9 weeks. The families in thecontrol group were not given the material and were not included in the sessions. MFSEP implementations were carried out witha hybrid model where face-to-face and distance education technologies are used together. The families in the experimental andcontrol groups were subject to pretest and posttest applications at the beginning and end of the sessions, respectively. Moreover,qualitative data were gathered from the families in the experimental group through a semistructured interview form. The results ofthis study indicated that MFSEP participants differed with respect to self-efficacy levels statistically and that MFSEP made a positiveand significant contribution to the development levels of the children of MFSEP participants owing to the developmental activitiesthat were offered and implemented by parents with their children at home.